COMPUTER TRANSFORMATION A SOLID REGULAR POLYHEDRONS ( PLATO’’S FIGURES) IN AUTOCAD SYSTEM TETRAHEDRON - Bezditko, P. V.; Krasnyuk, A. V.; Malyi, A. D.; Bocharova, N. P. (Science and Transport Progress, 2010)
In the article the technologies of transformation of a perfect polyhedron (tetrahedron) into semi-perfect one, starlike and imperfect polyhedrons by the methods of computer graphics are presented. The authors have concluded that such transformations of solid models of polyhedrons are most expedient from the known ones in descriptive geometry and engineering graphics.